Association between toxocariasis seropositivity and serointensity and cognitive function in older U.S. adults - Erickson, Lance D; Hedges, Dawson; Stone, Allison; Brown, Bruce L; Embley, Bradley; Gale, Shawn D (Folia parasitologica, 2022)
The nematodes Toxocara canis (Werner, 1782) and Toxocara cati (Schrank, 1788) have been associated with worse human cognitive function in children and middle-aged adults. In this study, we sought to determine the association between Toxocara seropositivity and serointensity determined by detection of IgG antibodies against the Toxocara antigen recombinant Tc-CTL-1 and cognitive function in older adults, including approximately 1,350 observations from the 2013-2014 National Health and Nutrition Examination Survey. Mean fluorescence intensity was used to quantify IgG antibodies against the Toxocara recombinant Tc-CTL-1 antigen, and respondents were considered positive at values greater than 23.1. In adjusted models from sample sizes ranging from 1,274 to 1,288 depending on the individual cognitive task, we found that Toxocara seropositivity was associated with worse performance on the animal-fluency task (b = -1.245, 95% CI: -2.392 to -0.099, P< 0.05) and the digit-symbol coding task (b = -5.159, 95% CI: -8.337 to -1.980, P< 0.001). Toxocara serointensity assessed using log-transformed mean fluorescence intensity as a continuous variable was associated with worse performance on the digit-symbol coding task (b = -1.880, 95% CI: -2.976 to -0.783, P < 0.001). There were no significant associations with tasks assessing memory. Further, age modified the association between Toxocara and cognitive function, although sex, educational attainment, and income did not. These findings suggest that Toxocara might be associated with deficits in executive function and processing speed in older U.S. adults, although additional research is required to better describe cognitive function in older adults who are seropositive for Toxocara spp.
Keywords: Cognition; toxocariasis; Immunoglobulin G; Nutrition Surveys; kognice; zvířata; cognition; imunoglobulin G; Animals; toxokaróza; National Health and Nutrition Examination Survey; Toxocariasis; Toxocara cati; Toxocara canis; výživa - přehledy; Toxocara